2009
DOI: 10.1097/rct.0b013e31818af37c
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Tube Current in Coronary Multidetector Computed Tomography Angiography

Abstract: Scout imaging can be used to determine individual patient habitus; habitus-adjusted minimal radiograph tube current cutoff levels identified in this study ensuring clinically required levels of coronary enhancement can be used for future coronary CT angiography optimization of tube current based on scout imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, reduction in radiations delivered during CCTA to the lowest acceptable dose should be a goal for every CT examination. In the past, several approaches have focused on reducing the effective radiation dose during CCTA examinations ( 16 , 17 , 18 , 19 ). Large trails have authenticated the use of BMI to adjust radiation dose by modulating tube voltage or current settings in CCTA ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reduction in radiations delivered during CCTA to the lowest acceptable dose should be a goal for every CT examination. In the past, several approaches have focused on reducing the effective radiation dose during CCTA examinations ( 16 , 17 , 18 , 19 ). Large trails have authenticated the use of BMI to adjust radiation dose by modulating tube voltage or current settings in CCTA ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Large trails have authenticated the use of BMI to adjust radiation dose by modulating tube voltage or current settings in CCTA ( 9 , 10 ). It has been reported that adaptation of tube current settings to BMI results in constant image noise and reduced radiation dose ( 10 , 16 ). However, adaptation of tube voltage is also important for reduction in radiation dose, as dose changes with the square of the tube voltage ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%